The Influence of Self-Control on the Learning Discipline of Students of SMKN 1 Katingan Kuala Katingan - Hasanah, Siti; Fahmi, Fahmi; Hidayati, Sri (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2023)
Learning discipline makes students regular in learning to produce good achievements, to produce good achievements cannot be separated from the quality of self-control. This study aims, 1) to determine the self-control of students at SMKN 1 Katingan Kuala Kabupaten Katingan, 2) to determine the PAI learning discipline of students at SMKN 1 Katingan Kuala, Kabupaten Katingan, 3) to determine the effect of self-control. The research method used in this research is quantitative. The population of this study was all students of SMKN 1 Katingan Kuala, Katingan Regency, totaling 90 people. The results of this study indicate, 1) the self-control of students at SMKN 1 Katingan Kuala Kabupaten Katingan in the high category with an average value of 121.86 in the interval 103-126, 2) PAI learning discipline of students at SMKN 1 Katingan Kuala Kabupaten Katingan in the high category. with an average value of 121.74 in the interval 103-126, 3) there is a positive and significant influence on self-control in the discipline of learning PAI students of SMKN 1 Katingan Kuala Kabupaten Katingan. This matter can seen from the calculation results obtained by rcount of 0.764 > rtable of 0.207 and the value of sig. 0.000<0.05.